2020
DOI: 10.1523/jneurosci.2324-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Mitochondria Modulation of LPS-Induced Neuroinflammation

Abstract: Neuronal mitochondria dysfunction and neuroinflammation are two prominent pathological features increasingly realized as important pathogenic mechanisms for neurodegenerative diseases. However, little attempt has been taken to investigate the likely interactions between them. Mitofusin2 (Mfn2) is a mitochondrial outer membrane protein regulating mitochondrial fusion, a dynamic process essential for mitochondrial function. To explore the significance of neuronal mitochondria in the regulation of neuroinflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 65 publications
2
53
0
1
Order By: Relevance
“…Levels of IL-1β have been shown to be elevated in AD brains [ 30 , 84 ]. Moreover, studies have suggested that neuroinflammation triggered by IL-1β impairs mitochondrial function [ 25 , 62 , 63 ]. Anakinra, a recombinant IL-1R antagonist [ 36 , 65 ], prevented AβO-induced mitochondrial dysfunction and alterations in MFN-1 and MFN-2 levels in mixed hippocampal cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of IL-1β have been shown to be elevated in AD brains [ 30 , 84 ]. Moreover, studies have suggested that neuroinflammation triggered by IL-1β impairs mitochondrial function [ 25 , 62 , 63 ]. Anakinra, a recombinant IL-1R antagonist [ 36 , 65 ], prevented AβO-induced mitochondrial dysfunction and alterations in MFN-1 and MFN-2 levels in mixed hippocampal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings implicate altered mitochondrial dynamics in IL-1β-mediated synaptic and memory defects and are consistent with studies showing that blockade of IL-1R restores cognition and alleviates pathogenesis in AD mouse models [ 26 , 27 ]. While the role of neuroinflammation on neuronal mitochondrial dynamics in AD has not been completely explored, there is evidence showing that production of inflammatory mediators can impair mitochondrial function [ 63 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for the variation in the effect of propofol on cell viability could be differences in cell origin, as cells derived from different sources could show variations in sensitivity to stimuli. For example, neurons are vulnerable to external insults, including LPS exposure and oxygen-glucose deprivation (OGD) [21][22][23], while microglia show a much higher tolerance to environmental changes. Another possible explanation for the variation in the effect of propofol on the viability of neurons and microglia could be the heterogeneity of GABA A receptor subunits within the brain [24].…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of AD is neuroinflammatory changes within the cortex, thought to be both a result and cause of cell death. One of the main drivers of the neuroinflammatory process are microglia – the brain's resident immune cells [5] . Activation of microglia in AD occurs as a response to cell damage, as microglia dispose of neuronal debris by phagocytosis.…”
mentioning
confidence: 99%